Compact ultra-wide band microwave filter utilizing quarter-wave length short-circuited stubs with reduced number of vias - Mohammad Shahrazel, Razalli; Alyani, Ismail; Mohd Adzir, Mahdi; Mohd Nizar, Hamidon (John Wiley & Sons Inc., 2009)
Link to publisher's homepage at http://www3.interscience.wiley.com